Household Waste Education of Kajartengguli in Sidoarjo Regency: Penyuluhan Sampah Rumah Tangga Desa Kajartengguli Kabupaten Sidoarjo - Marodiyah, Inggit; Cahyana, Atikha Sidhi; Nurmalasari, Intan Rohma (Universitas Muhammadiyah Sidoarjo, 2022)
Garbage is a problem for the community and the government. Moreover, according to data from KLH (2021) more than 50% of the total garbage in the community are household waste, because majority of the waste is remnants of daily activities. In addition to having an environmental impact, waste aesthetically reduces beauty and affects health with the appearance and smell it causes. To minimize the impact of waste, there must be some kind of activities to manage waste such as reducing and handling the produced waste. The problem faced by PKK women in Kajartengguli Village is how to manage and handle household waste which is increasing day by day, especially non-organic waste that cannot be decomposed. Which, all this time, the garbage was burned. This situation causes the environment to become less clean and tends to be underestimated. This community service activity aims to provide knowledge and socialization to the community about waste and its management to provide benefits such as increasing income by managing non-organic waste. The method is to conduct socialization related to waste and its use, provide counseling and assistance in managing non-organic waste into products that can be sold. This outreach and counseling was carried out through PKK Women in Kajartengguli Village by bringing in expert from the waste management staff of the Sidoarjo Regency Environmental Agency. The results of this activities showed that PKK women responded well in dealing with the waste generated. In addition, the level of understanding of the 3Rs, namely reduce, reuse and recycle has increased.